The Inflammatory Cytokine Imbalance for Miscarriage, Pregnancy Loss and COVID-19 Pneumonia - Vesce, Fortunato; Battisti, Chiara; Crudo, Michele (Frontiers in Immunology, 2022)
Pregnancy is a vascular event upon endocrine control. In the human hemo-chorial placentation the chorionic villi penetrate the wall of the uterine arteries, to provide increasing amounts of nutrients and oxygen for optimal fetal growth. In any pregnancy the natural maternal response is of a Th1 inflammatory type, aimed at avoiding blood loss through the arteriolar lesions. The control of the vascular function, during gestation is achieved through the action of two main types of prostanoids: prostaglandin E2 and thromboxane on the one hand (for vasoconstriction and coagulation), prostacyclin on the other (for vasodilation and blood fluidification). The control of the maternal immune response is upon the responsibility of the fetus itself, which changes the inflammatory Th1 type into the anti-inflammatory Th2. Research address to inflammation as the leading cause of abortion, pregnancy loss, premature delivery and related fetal syndromes. Increased level of Interleukin 6, Interleukin 1-beta, Tumor Necrosis Factor-alfa, Interferon-gamma, are some among the well-known markers of gestational inflammation. On the other side, COVID-19 pneumonia is a result of extensive inflammation induced by viral replication within the cells of the respiratory tract. As it may happen in the uterine arteries in the absence of an effective fetal control, viral pneumonia triggers pulmonary vascular coagulation. The cytokines involved in the process are the same as those in gestational inflammation. As the fetus breathes throughout the placenta, fetal death from placental thrombosis is similar to adult death from pulmonary thrombosis. Preventing and counteracting inflammation is mandatory in both conditions.